Lowering Blood Pressure Through Family Assistance on the Implementation of Self-Management of Hypertension Elderly - Rasmawati Rasmawati; Eny Sutria; Ani Auli Ilmi; Rasdiyanah Rasdiyanah; Aidah Fitriani; Muhammad Saleh Ridwan (LPPM Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Hypertension is one health problem that continues to increase in the elderly age group. The increasing prevalence of hypertension from year to year requires treatment efforts, one of which is through hypertension care management. Treatment of hypertension by the family involves knowledge and skills, so there is a need for assistance from health workers to caregivers who care for the elderly with hypertension. This study aimed to provide an understanding of the family and direct application to care for the elderly with hypertension. The research is a case study involving six families and elderly clients with hypertension. Respondents are elderly who have hypertension and still live with their families as caregivers. Interventions are carried out in the form of assistance to families in implementing control of taking hypertension medication, stress management, physical exercise, and regulation of eating patterns. Results: all of the elderly experienced a decrease in blood pressure on the 3rd weekend. Family assistance in the implementation of self-management of the elderly effectively reduced the blood pressure of the hypertensive elderly. Health center staff are expected to be able to increase motivation and family participation in assisting the elderly with hypertension.